(untitled) (Medico Legal Update, 2021)
Background: The COVID-19 has created havoc all over the world as no specific treatment available till date. Total COVID-19 cases had crossed 11,125,245 including 528,204 deaths as per the WHO data till 5 July 2020. Unfortunately, India secured third place in total tally of COVID-19 cases with 6,77,719 total cases including 19693 deaths as of 5th July 2020. The antiviral drug, Favipiravir, previously known as T-705 approved in Japan for treatment of Influenza. It is selective & potent inhibitor of viral RNA polymerase. It is promising drug for treatment of wide range of RNA viruses including SARSCoV-2. Method: The systematic review of Articles was done with the help of search engines like Embase, Medline, PubMed & Google Scholar, clinicaltrials.gov. The Peer reviewed articles published through 6th of July 2020 were included in the study. This review was done to establish clinical evidence for use of Favipiravir in COVID-19. Conclusion: It was found that due to lack of conclusive evidence, Favipiravir cannot be included in main armamentarium for COVID-19.